PENGARUH LOAN TO DEPOSIT RATIO (LDR) DAN BIAYA OPERASIONAL DAN PENDAPATAN OPERASIONAL (BOPO) TERHADAP RETURN ON ASSETS (ROA) PADA BANK BUMN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Laynita Sari; Hesti Yulisa Fitri (Sekolah Tinggi Pariwisata Mataram, 2022)
Return on Assets is a method of comparing the profits that have not been taxed with the number of assets owned by the bank, the comparison will state the level of efficiency of asset management applied by the related banking company. Bank Indonesia, which acts as the central bank, also prioritizes the value of a bank's profit whose value is measured by the ROA system method. The higher the ROA value of a bank can indicate the prospect of the performance of the banking institution increasing and getting better, this is because the rate of return (return) is getting bigger in value. the effect of Loan to Deposit Ratio and Operational Costs and Operating Income on state-owned banks listed on the Indonesia Stock Exchange in 2013-2020. The method used in this study is quantitative. The sampling in this study used purposive sampling and obtained 4 state-owned banks. The analysis technique in this research is panel data regression. The results of this study indicate that the Loan to Deposit Ratio has a positive effect on Return On Assets, while Operational Costs and Operating Income have no effect on Return On Assets.